2010
DOI: 10.1074/jbc.m110.113118
|View full text |Cite
|
Sign up to set email alerts
|

The Hsp40 J-domain Stimulates Hsp70 When Tethered by the Client to the ATPase Domain

Abstract: Hsp70-family molecular chaperones have numerous constitutive and stress-induced roles that involve binding to short hydrophobic stretches within a client protein. Protein folding, protein translocation, and protein disaggregation are a few of the functions that Hsp70s carry out under normal conditions within the cell (1-4).The two major activities of Hsp70s are located in the two major domains of the protein. The N-terminal 44-kDa domain binds and hydrolyzes ATP, and the 23-kDa peptide binding domain binds cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 44 publications
1
13
1
Order By: Relevance
“…There is a small, but very significant, difference between the data of Landry and coworkers (13,23) and ours: They also observed chemical shift changes for residue Asp35 of the conserved HPD loop. However, we found that shifts for the NH signal of Asp35 can also be caused by very small changes in ionic strength.…”
Section: Resultscontrasting
confidence: 48%
“…There is a small, but very significant, difference between the data of Landry and coworkers (13,23) and ours: They also observed chemical shift changes for residue Asp35 of the conserved HPD loop. However, we found that shifts for the NH signal of Asp35 can also be caused by very small changes in ionic strength.…”
Section: Resultscontrasting
confidence: 48%
“…This J-fusion bound much tighter to DnaK in the presence of ATP (0.2 nM) than in the absence of nucleotide (30 nM). A later paper of the same group using the same construct and using NMR spectroscopy to monitor binding to several DnaK constructs in different nucleotide states confirmed their earlier observations 159 . SPR experiments by Gross and co-workers 155 strongly suggest that wt-DnaJ binds tightly to the ATP state (K D = 70 nM) but does not bind to DnaK in the ADP state (i.e.…”
Section: The Role Of Dnaj In Allosterysupporting
confidence: 59%
“…Based on interaction studies using 15 N-line broadening analysis of DnaK with a chimeric protein consisting of a J-domain and a DnaK client protein (p5), it was shown that the chimera showed a stronger binding affinity towards DnaK and revealed novel insight into the functional interplay of DnaJ and DnaK. In conclusion, these results suggest that the J-domain shifts the equilibrium of DnaK to a substrate-bound form, enabling more productive binding of the substrate with subsequent stimulation of the ATPase function of DnaK [161]. Subsequent determination of the solution structure of the complex of DnaK with the J-domain of DnaJ in the ADP state and in the presence of a substrate peptide confirmed the interaction via helix II of the J-domain with a negatively charged loop in the Hsp70 nucleotide-binding domain.…”
Section: Dnakmentioning
confidence: 76%